Analysis Of The Factor Of Green Purchasing Behavior On The Customer's Bottled Mineral Water - Dian Kusmana; Yolanda Masnita; Kurniawati (Jurnal Manajemen, 2023)
The goal of this study is to examine the Green Purchasing Behavior factor in customers' bottled mineral water purchases. Data were collected from 192 respondents who consume bottled mineral water in Jakarta. In this study, quantitative research methods are used to analyze the validity, reliability, descriptive statistics, and Fit Model with Structural Equation Modeling (SEM). The results show that Environmental Advertisement has a significant effect on Environmental Knowledge, Environmental Advertisement has a significant effect on Eco Brand, Environmental Advertisement has a significant effect on Green Purchasing Behavior, Eco Brand has a significant effect on Green Purchasing Behavior Customer's bottled mineral water, and Environmental Knowledge has a significant effect on Eco Brand Customer's bottled mineral water. The managerial implication of this research is important for the community to choose bottled drinking water products that are low in pollution or environmentally friendly in order to increase the go green program in Jakarta.